2015
DOI: 10.1080/09297049.2015.1012491
|View full text |Cite
|
Sign up to set email alerts
|

Executive and attentional contributions to Theory of Mind deficit in attention deficit/hyperactivity disorder (ADHD)

Abstract: Attention deficit/hyperactivity disorder (ADHD) in children has been associated with attentional and executive problems, but also with socioemotional difficulties possibly associated with deficits in Theory of Mind (ToM). Socioemotional problems in ADHD are associated with more negative prognoses, notably interpersonal, educational problems, and an increased risk of developing other psychiatric disorders that emphasize the need to clarify the nature of their ToM deficits. In this study, we hypothesized that To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
76
0
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(89 citation statements)
references
References 60 publications
6
76
0
7
Order By: Relevance
“…For instance, another study of our laboratory found higher interference in children with ADHD compared to typically developing children with the same counting Stroop task. 67 Finally, we cannot discard a possible placebo effect on Stroop interference that has already been described in previous studies. 68 ADHD features severity was similar between placebo and osmotic-release oral system methylphenidate groups and is, thus, not responsible for the observed differences between groups.…”
Section: Discussionmentioning
confidence: 94%
“…For instance, another study of our laboratory found higher interference in children with ADHD compared to typically developing children with the same counting Stroop task. 67 Finally, we cannot discard a possible placebo effect on Stroop interference that has already been described in previous studies. 68 ADHD features severity was similar between placebo and osmotic-release oral system methylphenidate groups and is, thus, not responsible for the observed differences between groups.…”
Section: Discussionmentioning
confidence: 94%
“…Only a small number of the discussed studies tried to control social-cognitive ability for non-social-cognitive ability [35,43,48,58,75]. However, as neurocognitive deficits contribute to ToM impairment in other psychiatric disorders [84,85], it is probable that they would also be partly responsible for ToM deficits observed in depression. Another confounding factor may be the possible effect of medication on social cognition.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, ToM itself remains intact, but there is a failure to express this ability (Papadopoulos et al, 2005; Sodian and Hulsken, 2005). Supporting this view, Mary et al (2016) hypothesize that ToM dysfunctions in children with ADHD could be due to attentional or executive deficits. They found that children with ADHD performed worse than neurotypical children on all the EF tests (inhibition, planning, attention) and two higher-order ToM tasks.…”
Section: Introductionmentioning
confidence: 99%